Eﬀects of psyllium husk utilization on the efciency of feed utilization and the fecal hairballs elimination - Sornsadanant, Pwich; Kovitvadhi, Attawit; Poungpong, Kanokporn; Kongmun, Phongthorn (Food Agricultural Sciences and Technology, 2025)
The aim of this research is to examine the impact of psyllium husk utilization on the nutrition of cats and the reduction of fecal hairballs. A hybrid breed (Maine Coon × Persian) totaling 18 animals, mixed genders, with an average age of 2.58 ± 1.04 years and weight of 4.07 ± 1.22 kilograms, were included in a randomized completely block design. All cats were randomly assigned to receive three fiber-enriched food treatments: control (T1), 1% psyllium husk (T2), and 1% psyllium husk plus 6% cellulose (T3). Water was available ad libitum throughout the 30-day duration. The results showed that the control group (T1) exhibited lower feed intake (g/d) compared to the fiber groups (T2, T3) (P = 0.022). When analyzing feed intake relative to body weight (g/BW), the control group (T1) also showed lower values compared to the fiber groups (T2, T3) (P = 0.049). Fecal production (as-is basis) was highest in the group receiving 1% psyllium husk (T2) (P = 0.023), and significantly greater than the group receiving psyllium husk plus cellulose (T3) (P = 0.032). However, the use of psyllium husk and cellulose did not influence the total trichobezoar levels (P > 0.05). This study concludes that incorporating psyllium husk at a concentration of 1% increased feed intake and led to a higher wet fecal output, without significantly affecting trichobezoar reduction.